Earlier age of onset in multiple system atrophy with smoking and heavy alcohol use. (September 2019) - Jackson, Lauren; Coon, Elizabeth A.; Ahlskog, J. Eric; Bower, James H.; Sandroni, Paola; Benarroch, Eduardo E.; Mandrekar, Jay N.; Low, Phillip A.; Singer, Wolfgang
Abstract: Objective: To determine whether smoking or alcohol use impacts the age of onset and disease duration in multiple system atrophy (MSA). Methods: All patients diagnosed with MSA at Mayo Clinic, Rochester between 1998 and 2012 completed standardized questionnaires surveying smoking and alcohol use at the time of presentation. Results: Of 551 patients with smoking and alcohol use data, 281 were past or present smokers with age of onset of 60.76 years compared to 62.97 years in controls ( p  = 0.0144). Age of onset in the 87 heavy alcohol users was 56.87 years compared to 62.97 years in controls ( p  = 0.0133). There was no difference in disease duration for smokers ( p  = 0.2758) or heavy alcohol users ( p  = 0.4820) compared to controls. Conclusion: Our findings show that smoking history and/or heavy alcohol use is associated with younger age of onset in MSA but do not influence survival. Highlights: MSA patients with past or present smoking had earlier age of onset compared to MSA patients with no smoking history. MSA patients with history of heavy alcohol use had earlier age of onset and higher frequency of ataxia. History of both smoking and heavy alcohol use contributes to earlier onset in MSA of 4.3 years. Neither smoking history nor heavy alcohol use influenced overall survival in MSA patients.